Synthesis of 2′-Deoxy-2′-β-fluoro-4′-azido-5-fluorouridine as a Potential Anti-HIV Agent - Hou, Jiao; Wang, Jian-Hua; Yu, Wenquan; Chang, Junbiao (Synlett, 2023)
2′-Deoxy-2′-β-fluoro-4′-azido-5-fluorouridine, a new pyrimidine nucleoside analogue of azvudine (FNC), was designed and synthesized. The synthesis of this nucleoside analogue was achieved by bromination of 1,3,5-O-tribenzoyl-2-deoxy-2-fluoro-d-arabinofuranoside, followed by reaction with silylated 5-fluorouracil and further modifications of the sugar moiety, in a 7.6% overall yield over nine steps. The product exhibited good antiviral activity against HIV-1 infection in HEK293T cells.
Keywords: deoxyfluoroazidofluorouridine; nucleoside analogues; medicinal chemistry; anti-HIV-1 activity